Public Service Through Online Single Submission: Efforts to Simplify Investment Licenses in Improving Public Service - Sinulingga, Tommy Aditia; Satoto, Sukamto; Sirait, Ningrum Natasya; Affila (Ultimate Journal of Legal Studies, 2023)
Public service is a form of service that is principally the responsibility of and implemented by Government Agencies. One form of public service carried out by the government is related to investment licensing, namely through Online Single Submission (OSS). Online Single Submission (OSS) is a Business License issued for and on behalf of the minister, head of institution, governor, or regent/mayor to Business Actors through an integrated electronic system. However, the concern is whether Online Single Submission (OSS) will facilitate investment licenses or instead make it difficult in public services and whether Online Single Submission (OSS) is sufficiently safe, reliable and protected by law.This research is a normative juridical research, which is a legal research method carried out by examining library materials or secondary materials such as laws and regulations, books, legal rules and literature related to the formulation of this research problem. The data used is secondary data, which is obtained from primary legal materials, secondary legal materials and tertiary legal materials. The data collection method used in this research is library research by tracing, reading, studying or analyzing materials, theories and concepts. The making and issuance of investment license decree is a legal action of the government. As a legal action, there must be authority granted by legislation or it must be based on the principle of legality. The matter of investment license is regulated in Law No. 23 Year 2014 on Local Government, Law No. 25 Year 2007 on Investment is obtained. Online Single Submission has been categorized as providing improvements in public services but still must receive attention from the government.